2007
DOI: 10.1130/g23716a.1
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of the active faulting in central Mongolia

Abstract: We present remote-sensing and fi eld observations of an ~350-km-long east-west left-lateral strike-slip fault (the South Hangay fault) in the Hangay Mountains of central Mongolia, an area previously believed to be deforming solely by slip on scattered, and randomly oriented, normal faults. The known dip-slip faults are shown to be short segments introduced at bends in the much longer strike-slip fault. Our observations show that the active faulting in the Hangay Mountains is consistent with the regional strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 15 publications
4
62
0
5
Order By: Relevance
“…Many of the active faults have slip vectors consistent with the regional east-west left-lateral shearing measured by GPS (Calais et al 2003). Walker et al (2007Walker et al ( , 2008 identified a number of east-west left-lateral fault systems, all showing evidence of activity in the late Quaternary, within the western and southern parts of the Hangay Mountains (Fig. 1).…”
Section: Tectonic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the active faults have slip vectors consistent with the regional east-west left-lateral shearing measured by GPS (Calais et al 2003). Walker et al (2007Walker et al ( , 2008 identified a number of east-west left-lateral fault systems, all showing evidence of activity in the late Quaternary, within the western and southern parts of the Hangay Mountains (Fig. 1).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…However, there is uncertainty as to whether the slip vectors on the normal faults are consistent with the regional strain field or whether they respond purely to the local extensional stresses associated with doming (e.g. Baljinnyam et al 1993;Cunningham 2001;Walker et al 2007Walker et al , 2008. Determining the slip vectors of the normal faults, and hence determining whether they are compatible with the regional strain field, will help to distinguish between the differing scenarios.…”
Section: Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in the Nd isotope values between the Triassic strata in the THS on the northern Indian margin and the Tibetan terranes, along with early work indicating that the Triassic sediments in southeast Tibet were transported from a northern source, supports the early proposal that the Lhasa terrane and the Indian craton were both parts of the Gondwana; they were separated in the early Jurassic during the opening of the Neo-Tethys [3,15,16] . This geologic link suggests that Nd isotopic composition alone cannot be used as the sole criterion to differentiate Tibetan terranes from the Indian lithologic units [33,34] .…”
Section: Introductionmentioning
confidence: 97%
“…They are mainly concentrated on four major fault systems, which extend for several hundred kilometers. These strike-slip faults are potential fragile zones to come about large-magnitude earthquakes (Walker et al, 2007). The Mw 8.1 December 4th 1957 Gobi-Altai earthquake happened on the Bogd fault, it is an east-west trending leftlateral strike-slip fault (Kurushin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%